Taxonomic remarks on the Centaurea aeolica (Asteraceae) species complex - Brullo, Salvatore; Cambria, Salvatore; Crisafulli, Alessandro; Tavilla, Gianmarco; Sciandrello, Saverio (Phytotaxa, 2021)
In the course of a taxonomical revision of Centaurea aeolica and the closely related C. pandataria, species confined to the Aeolian Archipelago (N Sicily) and Ventotene island (Pontian Archipelago, Latium) respectively, we describe a new species, named C. phalacrica, occurring on coastal metamorphic rocks near Messina (NE Sicily). These three species, well differentiated in several features, are examined from morphological, nomenclatural, chorological, and ecological points of view. For each species, a detailed iconography, consideration on their conservation status and identification keys are provided too. The lectotype of C. pandataria kept in the Florence Herbarium (FI) is designated.